Advantages and disadvantages of working at university: estimates of scientific and pedagogical employees - G. Z. Efimova (Вестник университета)
In the article the focus of the research interest is directed to the advantages and limitations of work at university as assessed by scientiﬁc and pedagogical employees. The empirical study was conducted using the semi-structured interview method with 145 scientiﬁc and pedagogical employees from 7 leading Russian universities. The classiﬁcation of strengths (advantages) and weaknesses (disadvantages) of working at university has been formed, which are combined on the following grounds: organizational and managerial, social and academic, ﬁnancial and economic, and territorial and infrastructural. Advantages of working at university: favorable conditions for academic development; stable team of professionals and comfortable working atmosphere; lack of inertia and routine of the labor process; developed material and technical base and formed infrastructure of university; job stability and social guarantees. Disadvantages of working at university: high workload, which leads to emotional overwork and lower quality of work; bureaucratic procedures distract from the main work; lack of desired support from the management. Comprehensive work of university management, aimed at the systemic development of personnel policy, will eliminate the above- mentioned shortcomings and ensure the reduction of their occurrence risk. The obtained results of the sociological research can be used in practical work and in justiﬁcation of managerial decision-making by top management in universities, can be useful to other stakeholders such as scientiﬁc and pedagogical employees, graduate students, and young people oriented to employment in higher education institutions and building an academic career.